Serotonin 2C receptor agonists and the behavioural satiety sequence in mice. - Hewitt, K; Lee, MD; Dourish, C; Clifton, P (2002)
The studies reported here examined the role of the 5-hydroxytryptamine (5-HT)(2C) receptor subtype in the control of ingestive behaviour in mice. Behavioural satiety sequence (BSS) and food intake measurements were taken, comparing the selective 5-HT(2C) receptor agonist (S)-2-(6-chloro-5-fluoro-indol-l-yl)-l-methylethylamine hydrochloride (Ro 60-0175; 1.0, 3.0 and 10.0 mg/kg) and D-fenfluramine (3.0 mg/kg). Ro 60-0175 produced a dose-dependent decrease in food intake. The effects of Ro 60-0175 (3.0 mg/kg) on the BSS were similar to the hypophagic effects of D-fenfluramine (3.0 mg/kg). In a second experiment, the specific effects on feeding produced by Ro 60-0175 (5.6 mg/kg) were attenuated by pretreatment with the selective 5-HT(2C) receptor antagonist 6-chloro-5-methyl-1-[2(2-methylpyridyl-3-oxy)-pyrid-5-yl carbamoyl] indoline (SB 242084; 0.5 mg/kg). The 5-HT(1B/2C) receptor agonist 1-(m-chlorophenyl)piperazine (mCPP; 3 mg/kg) also produced a substantial decrease in food intake, which was attenuated by SB 242084 (0.5 mg/kg). A dose of the selective 5-HT(1B/1D) antagonist 2'-methyl-4'(5-methyl-[1,2,4]oxadiazol-3-yl)-biphenyl-4-carboxylic acid [4-(5-methoxy-3-(4-methyl-piperazin-1-yl)-phenyl]amide (GR 127935; 3.0 mg/kg) that successfully attenuated the action of the 5-HT(1B) agonist 5-methoxy-3(1,2,3,6-tetrahydropyridin-4-yl)-1H-indole (RU 24969; 5.0 mg/kg) failed to attenuate mCPP-induced hypophagia. These data suggest that Ro 60-0175- and mCPP-induced hypophagia in mice are mediated via activation of 5-HT(2C) receptors and that stimulation of 5-HT(1B) receptors plays only a minor role in mCPP-induced hypophagia.